2021
DOI: 10.1111/1365-2435.13780
|View full text |Cite
|
Sign up to set email alerts
|

Differential resistance and acclimation of two coral species to chronic nutrient enrichment reflect life‐history traits

Abstract: The effects of nutrient pollution on coral reef ecosystems are multifaceted. Numerous experiments have sought to identify the physiological effects of nutrient enrichment on reef‐building corals, but the results have been variable and sensitive to choices of nutrient quantity, chemical composition and exposure duration. To test the effects of chronic, ecologically relevant nutrient enrichment on coral growth and photophysiology, we conducted a 5‐week continuous dosing experiment on two Hawaiian coral species, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 72 publications
2
14
0
Order By: Relevance
“…The presence of species-specific variability in deoxygenation responses was not unexpected, considering that corals frequently show species level variation in bleaching susceptibility 32 , 39 and tolerance to other environmental conditions including pH 25 , 40 , nutrient enrichment 41 , and warming 42 , 43 . However, the magnitude of differential effects and temporal scale of response between A. cervicornis and O. faveolata was unexpected.…”
Section: Discussionmentioning
confidence: 95%
“…The presence of species-specific variability in deoxygenation responses was not unexpected, considering that corals frequently show species level variation in bleaching susceptibility 32 , 39 and tolerance to other environmental conditions including pH 25 , 40 , nutrient enrichment 41 , and warming 42 , 43 . However, the magnitude of differential effects and temporal scale of response between A. cervicornis and O. faveolata was unexpected.…”
Section: Discussionmentioning
confidence: 95%
“…It suggests that P. damicornis increases its reliance on dissolved inorganic N-sources (mostly NOx) when this resource dominates in the ecosystem (Grover et al, 2003). In Fox et al (2021) P. acuta colonies were cultivated under increasing nitrate concentration and symbionts continuously assimilated nitrate independently of the coral, increasing their density. If nitrate supplementation alone has been shown to be mostly detrimental to corals, Ezzat et al (2015) demonstrated that a combined enrichment of phosphate and ammonium at an appropriate stoichiometry (i.e., close to that of the coral tissues) was beneficial to the symbiosis.…”
Section: Seabird-derived Nutrient Supplies Modulate Pocillopora Damicornis Nutritionmentioning
confidence: 99%
“…Some species of Pocillopora have shown an exceptional trophic flexibility, being able to acquire nutrients through various degrees of autotrophy and heterotrophy (e.g., P. meandrina, Fox et al, 2019) which suggests that this genus is well suited to cope with variable N-supply. Paradoxically, this genus is not capable of regulating the nutrient uptake of its symbionts (Pocillopora sp., Fox et al, 2021). This lack of internal regulation makes this genus more prone to a nutritional imbalance, leading to a shift of the symbiosis toward parasitism, exacerbating bleaching susceptibility (Baker et al, 2018;Burkepile et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Coral responses to nutrient elevation are differential, varying by species, local nutrient history, and nutrient type, concentration, and ratio ( Bongiorni et al, 2003 ; Burkepile et al, 2020 ; Fabricius, 2005 ; Fox et al, 2021 ; Tanaka et al, 2017 ). A meta-analysis of historical nutrient research described how nitrogen enrichment oftentimes reduced calcification and enhanced photosynthesis in corals while, in contrast, phosphorous enrichment increased calcification with minimal effects on coral photosynthesis ( Shantz & Burkepile, 2014 ).…”
Section: Introductionmentioning
confidence: 99%